1977
DOI: 10.1212/wnl.27.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic hemorrhage

Abstract: An analysis has been made of the clinical manifestations in 18 cases of hypertensive thalamic hemorrhage diagnosed by computed tomography (CT). CT scans permitted accurate determination of the site, size, and extension of the hemorrhages. A sensorimotor hemiplegia or hemiparesis was present in all cases. Diagnostic clinical features included limitation of vertical gaze, downward deviation of the eyes, and small unreactive or sluggish pupils. All hemorrhages larger than 3.3 cm in diameter were fatal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
7

Year Published

1981
1981
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(37 citation statements)
references
References 0 publications
3
26
1
7
Order By: Relevance
“…(table 2) Few reports have appeared concerning the correlation between age and recovery in thalamic hemorrhage. Walsche et al 10 reported an average age of 79 years among 9 such deaths, and an average age of 54 among 9 such survivors. Nakahara et al, 12 however, reported that there is no correlation between age and recovery in this lesion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(table 2) Few reports have appeared concerning the correlation between age and recovery in thalamic hemorrhage. Walsche et al 10 reported an average age of 79 years among 9 such deaths, and an average age of 54 among 9 such survivors. Nakahara et al, 12 however, reported that there is no correlation between age and recovery in this lesion.…”
Section: Discussionmentioning
confidence: 99%
“…10, " Excluding the positive effects of continuous ventricular drainage or shunt operations in cases of thalamic hemorrhage, when ventricular dilatation or intraventricular hematoma is present, the size and site of the hematoma and the degree of brain damage at the site of the hemorrhage are thought to determine the degree of recovery following onset. For this reason, we considered that an investigation of factors in the acute stage which contribute to the prognosis in clinical cases would be particularly significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolic depression in thalamic hemorrhages is more extensive and persistent than in putaminal hemorrhages, which probably accounts for the reduced CBF and worse outcome in thalamic hemorrhages. While several studies have quoted a size of 3.3 cm as a determinant for survival in patients with thalamic hemorrhages [38][39][40] in a prospective trial that included 100 patients there were three survivors with hematomas larger than 3.3 cm who were able to lead independent lives [41]. However, sizes of the hematoma and intraventricular extension were two major factors that were found to correlate with the eventual outcome.…”
Section: Presentationmentioning
confidence: 99%
“…Intracerebral hemorrhage (ICH) constitutes 10% to 15% of all strokes and has a higher risk of morbidity and mortality then cerebral infarction and subarachnoid hemorrhage (SAH) 5 . The 30 day mortality ranges between 30% to 40% in hospital based studies 6,7 . Modifiable risk factors that increase the incidence of stroke include hypertension, smoking, alcohol, diabetes, dyslipidemia [8][9][10] beside some non-modifiable risk factors 11,12 .…”
Section: Introductionmentioning
confidence: 99%